Personal Financial Planning Industry in Malaysia: A Market Survey - Meysam, Safari; Shaheen, Mansori; Sesaiah, Stephen (2016)
The personal financial planning industry is a young industry in Malaysia. Over the last two decades, financial planners have come a long way to establish a foothold in a highly competitive and regulated finance industry. This study presents the results of a survey on the general public’s understanding about this profession by assessing the impact of five major influential factors on individuals’ intention tohire financial planners’ services. Awareness, acceptability,affordability, accessibility, and assurance are investigated as determinant contributors to such a decision. A structural equation model (SEM) analysis over survey data of almost 500 respondents from various states in Peninsular Malaysia indicates that with the exception of accessibility, all other factors are significantly important. The most critical factoris the acceptability of a financial planning service by the public. The second most critical factor is assurance (trust toplanner), awareness (existence of services), and affordability of financial planners’ services. Our results have policy aswell as industry implications. Awareness-making initiatives by government and policy making central agencies,trust-building behavior by practitioners and financial service providers, professionalism and transparency of practitioners,and competitive rates may lead to a higher penetration of financial planning services in Malaysia.